Japanese Village entrance and Tokio Cafe, Pay Streak, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: Japanese Village. Printed on verso: 75. The Japanese Village. The Japanese Village, or Streets of Tokyo, is at the foot of the Pay Streak, where everything Japanese is shown and vended. The Japanese theatre is the prominent attraction. 1909. The Alaska-Yukon-Pacific Exposition. Official Photograph. Published by Robert A. Reid. 488 Arcade. Made in Seattle. PH Coll 777 Reid.75 (See also PH Coll 78.193) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number